Strategi Pembelajaran PAI dalam Membentuk Akhlakul Karimah Peserta Didik di SDIT PUI Cibitung Tenjolaya - Masitho, Siti; Primarni, Amie; Paramansyah, Arman (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The thesis examined the learning strategies of Islamic Education in improving the students’ moral in in SD IT PUI Cibitung Tenjolaya. The aims of the study were to determine the learning strategies, describe the moral, as well as to analyze the impact of the learning strategies of Islamic Education teachers. The research was a qualitative descriptive study using spiritual, psychological, and pedagogical approaches. The data used were the primary and secondary data. The primary data sources were the school principal, vice principal, Islamic Education teachers, dormitory’s coaches, and other teachers. The secondary data sources were from the important documentation data, such as the school magazine, teachers’ and students’ data, as well as the data of infrastructure. The primary research instrument was the researcher himself, and it was developed by using observation guidelines, interviews, and documentation check. The data were then processed and analyzed through three stages, namely, data reduction, data presentation and conclusion. The results revealed that the learning strategies of Islamic Education used in SD IT PUI Cibitung Tenjolaya were inquiry, expository, cooperative, affective, and problem solving learning strategies, which involved a series of methods of exemplary, suggestion, question and answer, discussion, lecture, habituation, exercise, group work, assignment, punishment, and reward. The students’ moral was described by some assessment indicators such as their piety, discipline, relationship, hygiene, and responsibilities. As for the result of learning strategies against the students’ moral was well enough that they have started to be diligent in worship, discipline, responsible, relationship and self development, though it had not reached as expected, so the learning strategies should be further developed by looking for some learning strategies that can further improve the students’ moral